Emotional Intelligence on Psychological Wellness of Women IT Professionals, Bengaluru: A Structural Equation Modeling Approach - Samuel Mores Geddam, Kiran mai Yanamala, Dr. P. Lakshmi Prasanna (Journal of Informatics Education and Research, 2024)
Emotional Intelligence on Psychological Wellness of Women IT Professionals, Bengaluru: A Structural Equation Modeling Approach